2009
DOI: 10.1638/2007-0101.1
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in a Juvenile Green Sea Turtle (Chelonia mydas) Due to Ocean-Borne Plastic

Abstract: An emaciated 2.36-kg juvenile green sea turtle, Chelonia mydas, was found floating off of Melbourne Beach, Florida, USA (28 degrees 2'4"N, 80 degrees 32'32"W). The turtle exhibited signs of cachexia, positive buoyancy, lethargy, and obstipation; was covered with barnacles; and was anorexic at the time of presentation. Dorsal-ventral radiographs with positive contrast confirmed obstruction of the gastrointestinal tract. Serum chemistry abnormalities reflected metabolic/nutritional deficiencies. Gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…This may be the cause for the high ingestion selectivity seen in both pelagic and neritic turtles. Several studies have reported ingestion of balloons by sea turtles [11], [17], [52], [53], and anecdotal evidence exists for ingestion of balloons by whales and dolphins [54]. Worldwide cleanups sponsored by the Ocean Conservancy over the past 25 years have found over 1.2 million balloons, or about 0.7% of all debris items collected [55].…”
Section: Discussionmentioning
confidence: 99%
“…This may be the cause for the high ingestion selectivity seen in both pelagic and neritic turtles. Several studies have reported ingestion of balloons by sea turtles [11], [17], [52], [53], and anecdotal evidence exists for ingestion of balloons by whales and dolphins [54]. Worldwide cleanups sponsored by the Ocean Conservancy over the past 25 years have found over 1.2 million balloons, or about 0.7% of all debris items collected [55].…”
Section: Discussionmentioning
confidence: 99%
“…Due to natural curiosity, pinnipeds often become entangled in marine debris at a young age, which can constrict their body as they grow thus reducing quality of life (Allen et al 2012). Globally, at least 23 % of marine mammal species, 36 % of seabird species, and 86 % of sea turtle species are known to be affected by plastic debris (Stamper et al 2009). …”
Section: Effects Of Plastics On Marine Biodiversitymentioning
confidence: 99%
“…In Paraiba, Brazil, a turtle taken in for rehabilitation died after excreting 11 pieces of hard plastic and 9 pieces of plastic bag (Mascarenhas et al 2004). Similarly, a juvenile green sea turtle found minimally responsive, defecated over 74 foreign objects, including an array of different kinds of plastics while being rehabilitated (Stamper et al 2009). Prior to passing the debris, the turtle was consuming about 8 g of food per day.…”
Section: Sea Turtlesmentioning
confidence: 99%
“…Gastrointestinal obstruction may lead to chronic debilitation and eventually death (105). Cases of 492 secondary infection and mortality are frequently reported due to plastic ingestion (104,106).…”
mentioning
confidence: 99%